2010
DOI: 10.2485/jhtb.19.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Functionally Graded Hydroxyapatite for Large Mandibular Defects in Adult Rabbits

Abstract: Objectives: As an alternative to autograft harvesting, we develop a functionally graded hydroxyapatite (fg-HAp) to induce bone regeneration within extensive bone defects. The functionally graded crystallinity from the inside layer to the surface layer of the fg-HAp promotes bone remodeling and replacement. We evaluate the effects of fg-HAp alone and in combination with fibroblast growth factor (bFGF) on bone regeneration within a bone defect in a rabbit mandible. Methods: The bone defect in the rabbit mandible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In this way, HAP coatings improved the biological fixation, biocompatibility, and bioactivity of implants [85]. In addition, deposition methods such as spraying, sputtering, pulsed laser deposition, and sol-gel techniques have been attempted, and several reports have been published whereby bone formation was promoted by increasing cellular response [8688]. Furthermore, studies on bone regenerative applications have been carried out by mixing HAP with soft materials such as polymers to complement the drawbacks.…”
Section: Types Of Calcium Phosphatesmentioning
confidence: 99%
“…In this way, HAP coatings improved the biological fixation, biocompatibility, and bioactivity of implants [85]. In addition, deposition methods such as spraying, sputtering, pulsed laser deposition, and sol-gel techniques have been attempted, and several reports have been published whereby bone formation was promoted by increasing cellular response [8688]. Furthermore, studies on bone regenerative applications have been carried out by mixing HAP with soft materials such as polymers to complement the drawbacks.…”
Section: Types Of Calcium Phosphatesmentioning
confidence: 99%
“…55 Studies have suggested that both amorphous and crystalline phases in the coatings are desirable to promote a more stable interface with the biological environment. 56,57 Thinner HA layers, in the nanometer range, revealed increased cellular response than thicker HA layers. [58][59][60] Biomimetic nano-apatite coatings of porous titanium scaffolds resulted in an enhanced human osteoblast culture as well as greater bone formation in a canine bone in a growth chamber.…”
Section: Chemical and Physical Properties Of Hamentioning
confidence: 99%
“…In the case of notch type defect models in the rabbit model, multiple studies have evaluated defects of various sizes at different locations in the mandible with little consistency, leading to great difficulty in comparing results across these studies24252627282930313235394041. In Table 3, these studies are compared in terms of the size and location of the defect, age of the animal, type of fixation if any and methods of evaluation used.…”
Section: Discussionmentioning
confidence: 99%